THE 'OFF RECORD' POLITENESS STRATEGY IN THE CONVERSATIONS OF THE MAIN CHARACTER'S IN THE FILM INSIDIOUS: THE RED DOOR (2023) - Sitti Safinatul Askiyah (PROCEEDING OF NATIONAL SEMINAR ON LITERATURE, LINGUISTICS AND LANGUAGE TEACHING, 2026)
Off-Record Strategy in the Main Character's Conversation. Using Brown and Levinson's politeness theory and Grice's conversational implicature, the research examines how the main characters particularly Josh and Dalton Lambert, convey their fear, suspicion, and family conflict indirectly. The data are taken from selected dialogues in the film, which are analyzed qualitatively using discourse analysis. The findings show that off-record is realized through sarcasm, rhetorical questions, understatement, overstatement, and vague statements. These strategies function to protect the participants' face, manage tension, and indirectly express traumatic experiences related to the supernatural world. The study contributes to the understanding of pragmatic strategies in horror-family films and highlights how indirect communication strengthens emotional conflict in cinematic dialogues. The results further indicate that the use of off-record strategy is closely related to the violation of Grice's conversational maxims, which encourages the emergence of implicature in the dialogue. These violations allow the characters to communicate complex emotional states, such as fear and repression, without expressing them explicitly. In conclusion, off-record strategy plays an essential role not only as a politeness mechanism but also as a narrative device that enhances psychological depth and suspense in the film. It reflects the characters' internal conflicts while simultaneously engaging the audience in interpreting implied meanings within the dialogue